Discrimination in an unequal world - Centeno, Miguel Angel, 1957-; Newman, Katherine S., 1953- (New York ; Oxford : Oxford University Press, 2010)
Proponents of globalization argue that it is helping & that in a competitive world, no one can afford to discriminate except on the basis of skills. Opponents counter that globalization does nothing but provide a meritocratic patina on a consistently unequal distribution of opportunity.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Discrimination; Racism; Equality